Microbiological and Pharmaco-toxicological Profile of Nifuratel and its Favourable Risk/Benefit Ratio for the Treatment of Vulvo-vaginal Infections - Mendling, Werner; Mailland, Federico (Arzneimittelforschung, 2002)
Nifuratel (CAS 4936-47-4) is a furane-de-rivative provided with a strong tricho-monicidal activity equivalent to that of metronidazole (CAS 443-48-1); it has a broad antibacterial spectrum of action, including both Gram-negative and Gram-positive organisms. It is active against Chlamydia trachomatis and Mycoplasma spp. and has also some degree of activity against Candida spp. and mycetes. Its broad spectrum of action, confirmed by in vitro and in vivo studies, covers virtually all the micro-organisms responsible for the infections of the genito-urinary tract.Nifuratel has a very safe toxicological profile. It is practically non-toxic in acute tests in mice and rats and is also well tolerated after repeated oral and intravaginal administrations. Nifuratel is devoid of teratogenic effects.The comparison among past and recent clinical studies confirms that, in contrast to metronidazole, no resistance phenomena to the treatment with nifuratel are reported. The drug can be used during pregnancy due to the absence of teratogenic effects. In conclusion, nifuratel shows a very favourable risk/benefit ratio for the treatment of patients with vulvovaginal infections.
Keywords: CAS 4936-47-4; Inimur®; Macmiror®; Nifuratel, antimicrobial activity, pharmaco-toxico-logical profile, resistance phenomena; Vulvo-vaginal infections